CALCAREOUS NANNOFOSSILS FROM LATE JURASSIC SEDIMENTS OF THE VOLGA BASIN (RUSSIAN PLATFORM): EVIDENCE FOR PRODUCTIVITY-CONTROLLED BLACK SHALE DEPOSITION - Kessels K.; Mutterlose J.; Ruffell A. (My University, 2003)
The Jurassic/Cretaceous boundary interval in the northern hemisphere is characterized by the widespread occurrence of black shales. About 60% of all petroleum source rocks comprise sediments of late Jurassic and early Cretaceous age with the origin of such black shales still under discussion. In order to better understand the factors that controlled black shale sedimentation, 78 samples were analyzed for calcareous nannofossils from two sections (Gorodische, Kashpir) of the Volga Basin (NE Russia). Calcareous nannofossils are ideal proxies for deciphering nutrient, temperature and salinity fluctuations. Additionally 58 samples from both sections were also analyzed for clay mineralogy, δ13Corg , TOC and CaCO3 composition. Both sections contain calcareous claystones and intercalated organic rich shales overlain by phosphorite beds. The presence of the calcareous nannofossil species Stephanolithion atmetros throughout both successions allows a biostratigraphic assignment to the S. atmetros Nannofossil Biozone (NJ 17), which corresponds to the Dorsoplanites panderi Ammonite Biozone of the Middle Volgian. The marlstones of the Kashpir section yield a well-preserved rich and diverse nannoflora, whereas all black shale beds are essentially barren of calcareous nannofossils. Only the uppermost black shale layers yield an impoverished assemblage of low diversity and abundance. Geochemical data suggest an early diagenetic nannofossil dissolution in the black shales of the Kashpir section. This is supported by the occurrence of coccoliths in black shale horizons of the Gorodische section. The assemblages in both sections are dominated by coccoliths of the Watznaueriaceae group (Watznaueria barnesae, Watznaueria fossacincta, Watznaueria britannica, Watznaueria communis), Biscutum constans and Zeugrhabdotus erectus. In Kashpir rare specimens of Crucibiscutum salebrosum occur in the higher part of the section. These taxa indicate boreal affinities. B. constans and Z. erectus are considered to be taxa indicative of a higher productive environment, while C. salebrosum is a cool-water species. From base to top of the Kashpir section, consecutive mass occurrences of different taxa/groups were observed: W. barnesae–W. fossacincta acme, W. britannica–W. communis acme, Z. erectus acme, B. constans acme (including sparse occurrences of C. salebrosum). The observed distribution patterns have been interpreted as characterizing a transition from a low productive, oligotrophic setting with high abundances of K-selected cosmopolitan species (Watznaueriaceae) and predominating marlstone sedimentation to a higher productive, mesotrophic setting. Cooler water temperatures marked by r-selection and acmes of opportunistic species (Z. erectus, B. constans) are coincident with the deposition of black shales and phosphorites in the higher part of the section. Interpretation of clay mineral distribution indicates that black shale deposition occurred under semi-arid hinterland climatic conditions concomitant with a sea level rise. This induced dysoxic conditions in the deeper parts of the Volga Basin, favoring the preservation of organic matter. The cause of the nutrient enrichment in the surface water is still unclear, but possible river water input from the continents does not seem to have been the controlling factor under a semi-arid climate. The occurrence of phosphorites in the upper part of both sections presumably indicates that enhanced productivity may be better explained by the upwelling of nutrient-rich bottom water and thereby causing the recycling of nutrients from oxidized phytoplankton back into the photic zone. This recycling effect finally may have led to an intensified phytoplankton growth which seemed to be a sufficient source for the enrichment of organic matter. This is well correlated with the increase in black shale horizons in the upper part of the Kashpir section.
Keywords: Calcareous nannofossils; Late Jurassic; Black shales; Volga Basin; Paleoproductivity; Mesozoic::Jurassic; Мезозой::Юрская